PENGAMBILAN DATA KWH METER MENGGUNAKAN MIKROKONTROLER ATMEGA8535 DENGAN KOMUNIKASI INFRAMERAH - Agus Atabik Anwar; Kusworo Adi (Youngster Physics Journal, 2014)
Research has been done utilizing the infrared data communication, as data retrieval by officers PLN kwh meter, kwh meter analog works by utilizing a rotating magnetic field aluminum plate, the rotation speed is influenced by the size of the electric current, the data set will be taken manually every month by officers PLN. Analog kwh meters of electricity in this regard has been modified into a digital Kwh meter, with infrared transmitter facility as a data transmission media. In this research will be limited only in the manufacture of data communications equipment, utilizing the media wave infrared wireless transmission of data with a certain distance.            This Equipment will have an LCD and several buttons to facilitate the operation. Data  of  Kwh meter saved in the Equipment can be viewed again on the LCD. With the assistance of proper software, data can further be processed into a computer using comport feature on the Equipment. This Equipmentuses microcontroller ATmega8535 and 9-volt battery power. Keywords: microcontroller, infrared communication, Kwh meter